Advances in Low-carbon and Stainless Steels - Haghdadi, Nima; Somani, Mahesh (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue of Metals was dedicated to recent advances in low-carbon and stainless steels. Although these types of steels are not new, they are still receiving considerable attention from both research and industry sectors due to their wide range of applications and their complex microstructure and behavior under different conditions. The microstructure of low-carbon and stainless steels resulting from solidification, phase transformation, and hot working is complex, which, in turn, affect their performance under different working conditions. A detailed understanding of the microstructure, properties, and performance for these steels has been the aim of steel scientists for a long time. This Issue received quality papers on different aspects of these steels including their solidification, thermomechanical processing, phase transformation, texture, etc., and their mechanical and corrosion behaviors.